The Fontan and the Sea: First-in-Man Data on Swimming and Diving Physiology in Fontan Patients - Paech, C.; Gebauer, R. A.; Weidenbach, M.; Mensch, S.; Kalden, P.; Markel, F.; Michaelis, A.; Schöffl, Isabelle; Daehnert, I.; Riede, F. T.; Rudrich, P.; Wolfarth, B.; et al. (Pediatric Cardiology, 2021)
While swimming represents a popular recreational activity, the immersion of the human body into the water requires a complex physiologic adaption of the whole cardiopulmonary and circulatory system. While this sport is regarded as beneficial, especially in cardiovascular patients, current guidelines hypothesized a possible hazardous effect of swimming and especially diving in patients with univentricular hearts after Fontan palliation. Yet, actual data to underline or contradict these assumptions are lacking. Therefore, this study aimed to conduct a first feasibility study for the evaluation of these effects on Fontan physiology and elucidate the gap of evidence currently preventing patients after Fontan palliation from being restricted from swimming or diving on doctoral advice. Patients recruited from the Heart Center Leipzig, Department of pediatric cardiology, underwent spiroergometry treadmill testing followed by a spiroergometry swimming stress test in a counter current pool. Physiologic data were recorded. A short apnea diving test was performed. The current study found similar physiologic reactions comparing treadmill and swimming exercise stress testing. Heart rate response and oxygen uptake were comparable on land and in the water. This study presents the first-in-man data on swimming and diving in Fontan patients. In this small study cohort of three Fontan patients, there were no adverse events triggered by swimming and breath-hold diving seen. Basically, the physiologic response to exercise was comparable on land and in the water.
CRIS-Team WoS Importer:2021-06-11